Evaluation of everyday routine changes caused by rheumatoid arthritis (RA). Differences between genders - Marta Obrzud; Anna Gronek (Kazimierz Wielki University, 2018)
Rheumatoid arthritis is a chronic, inflammatory systemic auto-immunologic disease that affects the connective tissue. It is characterized by non-specific symmetrical inflammation of the synovial membrane, abarticular changes, and organic complications. The illness causes damage of structural and functional integrity of the musculoskeletal system whose consequences are disability and premature death of the individuals [28]. In this thesis the focus was particularly put on the problem of the quality of life with rheumatoid arthritis and the process of rehabilitation and education of the individuals affected with this disease. The problem of the struggle with pain has been pointed out as a significant factor in clinical treatment. 50 patients with diagnosed rheumatoid arthritis of University Clinical Hospital were the subjects of study. The study was performed using a special, self-designed questionnaire which assisted in analyzing four aspect of life: physical activity, work activity, social functions, and psychological condition of the patients. The conclusions suggest that this illness creates limitations in many spheres of life, and affects women more frequently. Pain and morning stiffness was the main problem reported by the studied individuals, as resulting in limitations in active work life , unattended activities and being dependent on other people. RA made patients limit their social contacts. The more the illness had progressed, the worse the quality of life became in all studied aspects, as reported by the studied patients.